Peer Instruction: Continuing Teacher Education in Higher Education - Vieira, Marili M. da Silva; Neto, Benedito Guimarães Aguiar (Procedia, social and behavioral sciences, 2016)
Teachers in higher education have little pedagogical information to support their practice; therefore, it is essential for universities to promote formal opportunities for teachers to reflect about their practices. Does a peer instruction program for in-service teachers continuing education offered one week per semester effectively promote changes in teachers’ pedagogical practices? This study aims to analyze if a week of peer instruction among teachers is an efficient program and to verify its effectiveness on pedagogical practices of teachers that experienced the program. In doing so, it also aims to point out the impressions that teachers have to improve the implemented program. For three years, the university promoted conferences and workshops on teaching practice for the teachers of undergraduate and graduate programs. The focus was on peer instruction, with a few outside and outstanding conference speakers on subjects related to teaching. After three years, teachers anonymously answered a questionnaire, which then received statistical analysis. The results were interpreted with theoretical support from Freire, Nóvoa, and Garcia. We found that more than half the teachers stated they had implemented changes in their daily practices related to the strategies they used and as a result of their studentś learning. The study points out that peer interaction, study, and instruction favors teacherś reflection on their daily practice and facilitates the attitude necessary for implementing changes in their routines. Involving teachers in their continued education is as important as presenting innovative teaching methodologies.